Nucleophile/Electrophile Combinations in Aromatic Substitution: From Wheland to Wheland–Meisenheimer Intermediates Using Strongly Activated Arenes - Micheletti, Gabriele; Boga, Carla (Synthesis, 2017)
This short review provides an overview on the interaction between 1,3,5-triaminobenzene derivatives and different kinds of electrophiles. Due to the ambident reactivity of these nucleophiles (i.e., at the nitrogen atom of the substituents and at the aromatic carbon atom) different compounds can be obtained. Particular attention is devoted to the detection, isolation, and characterization of covalent intermediates of aromatic substitution, starting from Wheland intermediates until the first detection and characterization of Wheland–Meisenheimer intermediates.1 Introduction2 Reactions between 1,3,5-Triaminobenzene Derivatives and Charged Electrophiles2.1 The Proton as an Electrophile2.2 Arenediazonium Salts as Electrophiles3 Reactions between 1,3,5-Triaminobenzene Derivatives and Neutral Electrophiles3.1 Alkyl Halides as Electrophiles3.2 Acyl Halides and Sulfonyl Chlorides as Electrophiles3.3 Aryl Halides and Heteroaryl Halides as Electrophiles3.4 Polynitroheteroaromatics as Electrophiles4 Conclusion
Keywords: reaction intermediates; aromatic substitution; triaminobenzenes; electrophiles; nucleophiles; Wheland complexes; Wheland–Meisenheimer intermediates